My Father's House : On Will Barnet's Paintings. - Dumm, Thomas (Duke University Press, 2014)
Political philosopher Thomas Dumm's wide-ranging reflections on a series of paintings by the American artist Will Barnet (1911-2012) depicting the artist's family members and childhood home.